EMPIRE, TRINITY, AND IRONY: RHETORIC AND THE BOOK OF REVELATION - Rian Venter (Acta Theologica)
The article investigates the question as to whether the use of an intentional reading approach, such as the rhetorical one, could generate innovative avenues for constructing a doctrine of God. The Book of Revelation is explored as case study. Three specific questions - about the rhetorical situation, the strategy, and the aim of Revelation - are discussed from the perspective of empire, triune God, and irony. A number of insights emerged as academic contribution of the study as a result of the methodological choice. A trinitarian naming of God was entangled with empire already at an early stage of Christianity. It was simultaneously implicated by and subversive of empire. In Revelation’s presentation of God one encounters redefined notions of divine agency and power, and an association with irony. The creative portrayal of the Divine enabled afflicted communities to navigate a way of life resistant of empire.